High-resolution melt curve analysis for rapid detection of rifampicin resistance in Mycobacterium tuberculosis: a single-centre study in Iran. (May 2020) - Arefzadeh, S.; Azimi, T.; Nasiri, M.J.; Nikpor, Z.; Dabiri, H.; Doustdar, F.; Goudarzi, H.; Allahyartorkaman, M.
Abstract: This study aimed to compare the diagnostic accuracy of high-resolution melting (HRM) analysis in comparison with Xpert MTB/RIF as well as conventional drug susceptibility testing (DST) for the detection of rifampicin (RIF) resistance in Mycobacterium tuberculosis in Iran. A comparative cross-sectional study was carried out from April 2017 to September 2018. A total of 80 culture-positive clinical samples selected during the study period were analysed for detection of RIF-resistant TB by conventional DST, Xpert MTB/RIF, and sequencing. Sensitivity and specificity of the HRM calculated according to DST was our reference standard test in this study. The overall sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of HRM assay were found to be 100%, 89.33%, 38.46%, and 100% respectively. The analysis demonstrated that the diagnostic accuracy of HRM tests is insufficient to replace Xpert MTB/RIF and conventional DST. HRM tests have the advantage of time to result and may be used in combination with culture. Further work to improve molecular tests would benefit from standardized reference standards and the methodology.